1988
DOI: 10.1021/j100328a007
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation energy of an isolated triplet acetone molecule

Abstract: The consideration of the second preequilibrium is made necessary by the finding that, in the route leading to tetrathionate, the concentrations of both thiosulfate and the hydrogen ion are on the second power.The catalytic effect of thiosulfate on the oxidation of hydrogen sulfite is explained by (M8) and (M9) I03H2S203-+ HSO3--» SO42-+ S2032" + IOf + 3H+ (M8) I03H2S203 + HSO3-+ H+ ^S042" + S2032" + I02-+ 4H+ (M9)These reactions, together with the preequilibria (M4) and (M6), are responsible for the third and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…1͒. 25 Hence, the impulsive model predicts an internal energy of 38 or 45 kcal/mol for the acetyl intermediate at the two energies studied. The rotational energy of CH 3 CO is taken to be ϳ1 kcal/mol.…”
Section: Resultsmentioning
confidence: 87%
“…1͒. 25 Hence, the impulsive model predicts an internal energy of 38 or 45 kcal/mol for the acetyl intermediate at the two energies studied. The rotational energy of CH 3 CO is taken to be ϳ1 kcal/mol.…”
Section: Resultsmentioning
confidence: 87%
“…Photolysis of acetone is one of the most extensively studied photochemical reactions [118]. The CC bond dissociation, called "Norrish type I reaction" (CH 3 ) 2 CO → CH 3 CO + CH 3 , has been the main focus of many theoretical and experimental studies [119][120][121][122][123][124][125][126][127][128][129][130][131][132][133]. Roaming was also suggested experimentally [102], which was proposed to proceed on the S 0 PES as (CH 3 ) 2 CO → CH 3 CO · · · CH 3 → CO + CH 3 -CH 3 .…”
Section: Photodissociation Of Acetonementioning
confidence: 99%
“…In early experimental studies [119][120][121], it was proposed that the Norrish type I dissociation occurs on the T 1 PES (the T 1 path) after an ISC from the S 1 PES, as long as the photon energy exceeds the barrier of the CC bond breaking on the T 1 PES. A theoretical calculation at the CASSCF level indicated that the ISC happens around a S 1 /T 1 -MSX structure located below the T 1 barrier, and the T 1 path was suggested to be the most preferable channel (at least in terms of potential energy) [122].…”
Section: Photodissociation Of Acetonementioning
confidence: 99%
“…At wavelengths longer than 305 nm, however, vibronic structure is observed. 4,5,18 Haas and co-workers 5 report fluorescence lifetimes which decrease dramatically with shorter wavelengths near 305 nm, indicating the onset of dissociation. A barrier height of 13.2 kcal/ mole was determined.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5,[13][14][15] Evidence for a sequential dissociation from this state includes the detection of acetyl radicals and the measurement of two resolved methyl translational energy peaks. 15 For photodissociation from S 2 , the first Rydberg state, however, the experimental evidence is less conclusive and conflicting interpretations have been presented, so that questions remain concerning the photodisso-ciation mechanism.…”
Section: Introductionmentioning
confidence: 99%